Degradation study of GaN-based high electron mobility transistors - Lius, Melina Novalia Jontera (Nanyang Technological University, 2023)
"Moore's Law" states that the number of transistors in an integrated circuit will increase twice roughly every two years. As observed since the 1970s, the number of transistors per silicon integrated circuit doubled every 18 months, consistent with this trend. This increase in transistor packing density has led to significant improvements in device performance. However, as transistors continue to shrink, limitations related to the fundamental properties of silicon, such as quantum physics of carrier transport, short channel effects, and lithography challenges, must be considered. Alternative materials with superior properties are being explored to manufacture semiconductor devices to achieve this goal. Wide bandgap semiconductors, for instance, the III-V compounds and SiC, have been well implemented in high-power electronic applications. Gallium Nitride (GaN) is a promising alternative among the III-V compounds due to its outstanding inherent material properties. Among all prospective semiconductors, integrating AlGaN/GaN high electron mobility transistor (HEMT) into a silicon (Si) substrate in a monolithic manner is an attractive and economical solution for extending the potential of silicon technology, particularly for high-power and high-frequency applications. Using Si substrate for GaN epitaxy is cheaper than other substrates such as Sapphire and SiC. It also enables integration with current Si technology in the industry. However, this technology still needs reliability issues that limit its potential. This study aims to investigate the correlation between the electrical and physical deterioration of Gallium Nitride (GaN) based high electron mobility transistors (HEMTs) grown on Silicon (Si) substrates while being exposed to different stressing conditions.